2018
DOI: 10.1634/theoncologist.2018-0580
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Trial Evaluating the Safety of a Shortened Infusion of Ramucirumab in Patients with Gastrointestinal Cancer

Abstract: Lessons Learned. A shortened infusion of ramucirumab (from 60 to 20 minutes) was safe and feasible without infusion‐related reactions. Twenty‐minute infusions of ramucirumab can be an option for patients with no infusion‐related reactions during the first 60‐minute treatment. Background. Ramucirumab is usually administered over 60 minutes, during which it is unlikely to cause infusion‐related reactions (IRRs). This prospective study eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Retrospective and prospective studies of various therapeutic antibodies (e.g., ramucirumab, bevacizumab, rituximab, daratumumab, and infliximab), with IRR incidence as an endpoint, have found that a more rapid rate of infusion/shortened infusion time does not appear to increase IRR incidence. For example, a recent small prospective study found no immediate IRRs in patients receiving ramucirumab infused over 20 min following at least one initial 60-min infusion without evidence of immediate IRRs [18]. Hence, the commonly held perception that immediate IRR incidence is related to infusion rate warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective and prospective studies of various therapeutic antibodies (e.g., ramucirumab, bevacizumab, rituximab, daratumumab, and infliximab), with IRR incidence as an endpoint, have found that a more rapid rate of infusion/shortened infusion time does not appear to increase IRR incidence. For example, a recent small prospective study found no immediate IRRs in patients receiving ramucirumab infused over 20 min following at least one initial 60-min infusion without evidence of immediate IRRs [18]. Hence, the commonly held perception that immediate IRR incidence is related to infusion rate warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%